Downregulation of Ras association domain family member 6 (RASSF6) underlies the treatment resistance of highly metastatic nasopharyngeal carcinoma cells. - Ying-Ying Liang (Public Library of Science (PLoS), 2014)
Radiation and cisplatin-based chemotherapy are major treatments for nasopharyngeal carcinoma (NPC). However, a major impediment for further improving the cure rate is the development of treatment resistance with an undetermined molecular mechanism in metastatic NPC cells. Our established, highly metastatic NPC cells have been reported to be more resistant to cisplatin chemotherapy. In the present study, we found that Ras association domain family member 6 (RASSF6) was downregulated in highly metastatic cells but upregulated in low metastatic cells in comparison to their parental cell line. Ectopic-expression of RASSF6 enhanced the sensitivity of highly metastatic NPC cells to cisplatin or radiation by enhancing apoptosis. RASSF6 depletion conversely reduced treatment sensitivity by decreasing the apoptosis rate. Over-expression of RASSF6 in highly metastatic NPC cells could enhance the phosphorylation of JNK when exposed to cisplatin or radiation treatment, while knocking down RASSF6 in low metastatic NPC cells could reduce the level of phospho-JNK when exposed to the same treatments. The activation of JNK signaling by RASSF6 and its subsequent sensitivity to apoptosis in NPC cells could be inhibited by applying the JNK inhibitor SP600125. In conclusion, the downregulation of RASSF6 in highly metastatic NPC cells contributed to their treatment resistance, and over-expression of RASSF6 conferred treatment sensitivity to highly metastatic NPC cells by activating JNK signaling. RASSF6 could be a valuable molecular marker for identifying sensitive metastatic NPC tumors during cisplatin treatment or radiotherapy.